On guard but not sworn: The relationship between school security guards, school resource officers, and student behavior, discipline, and arrests - Vernon, Keenen (Criminology & public policy, 2024)
Research Summary The increasing presence of armed security personnel in schools has led to concerns about the criminalization of students. While many schools use sworn law enforcement (e.g. school resource officers or SROs), many schools also use security guards who are not sworn law enforcement. Recent policy changes in a number of states and political pressures resulting from acts of mass school violence have led policymakers to face decisions between the use of SROs and security guards. This study informs this policy debate by empirically examining the relationships between security guards and SROs with rates of student behavior, discipline, and arrest using nationally representative data from the Civil Rights Data Collection. Controlling for observable covariates and school district fixed effects, we find that, in contrast to SROs, the use of security guards in schools is not systematically related to student arrest or suspension rates. The findings suggest that non-sworn security guards may provide a form of security personnel that minimizes the criminalization of students relative to SROs. Policy Implications As school districts nationwide grapple with how to respond to school shootings and other acts of school violence, policymakers have frequently turned to the use of school security personnel, including SROs and security guards, as a response. Doing so, however, has been contentious given concerns about the overcriminalization of students. This study provides evidence to inform these policy debates by demonstrating the relationships between security guards and SROs and a number of outcomes. The results suggest that the use of security guards as a policy response may minimize arrests and exclusionary discipline relative to the use of SROs.